Duet fortepianowy = Piano duo - selected reflections - Jankowska-Borzykowska, Katarzyna (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The paper focuses on 4 hands and 2 pianos playing as an essential part of piano curriculum. The paper discusses various aspects and specific problems, that such chamber formations face, in particular articulation, pedaling, narration and phrasing.
Keywords: gra na cztery ręce; dwa fortepiany; kameralistyka; pedalizacja; artykulacja; four hands; two pianos; chamber music; pedaling; articulation